Kepemimpinan Rusia, Amerika Serikat, Dan Israel Dalam Pengelolaan Sumber Daya Siber Sebagai Pembelajaran Bagi Doktrin Pertahanan Siber Indonesia - Syah Putra Siregar, Eko; Bagiono, Amin; Susilo, Tarsisius; Hadisuseno, Bungkus; Amperawan, Cahyadi (Jurnal Syntax Fusion, 2025)
The rapid advancement of digital technology has reshaped the global defense landscape, positioning cyberspace as a new strategic domain in the competition for national power. Countries such as Russia, the United States, and Israel demonstrate distinct leadership models in managing digital resources and developing resilient cyber defense systems. This study aims to analyze the characteristics of strategic leadership in these three nations and identify relevant lessons for the formulation of Indonesia’s cyber defense doctrine, characterized by national values and aligned with the vision of Indonesia Emas 2045. The research employs a qualitative descriptive method using a policy analysis approach through literature review and examination of official documents from defense institutions and international strategic studies. The findings reveal that the United States exhibits transformational and collaborative leadership, Russia demonstrates firm and centralized strategic-military leadership, while Israel reflects adaptive and innovative leadership driven by technological research. The synthesis of these models suggests that Indonesia’s cyber defense doctrine should integrate the values of Pancasila, strengthen cross-sector leadership among government, military, and technology industries, and promote defense research innovation to reinforce digital sovereignty and enhance national cyber resilience in the digital era.